VD_FINDINFO Jug / 2015 / 469 vom 5. Mai 2015 - VD Tribunal cantonal (2015)
FIXATION DE LA PEINE, CONSTATATION DES FAITS, DROIT D'ÊTRE ENTENDU, VIOL, CONTRAINTE SEXUELLE | 189 CP, 190 CP, 47 CP, 29 al. 2 Cst., 398 al. 3 let. b CPP (CH), 9 CPP (CH)